2005
DOI: 10.1128/mcb.25.12.5215-5225.2005
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of the SCL Locus: Identification of an Enhancer That Targets the Primitive Erythroid Lineage In Vivo

Abstract: The stem cell leukemia (SCL) gene, also known as TAL-1, encodes a basic helix-loop-helix protein that is essential for the formation of all hematopoietic lineages, including primitive erythropoiesis. Appropriate transcriptional regulation is essential for the biological functions of SCL, and we have previously identified five distinct enhancers which target different subdomains of the normal SCL expression pattern. However, it is not known whether these SCL enhancers also regulate neighboring genes within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(93 citation statements)
references
References 73 publications
(65 reference statements)
6
87
0
Order By: Relevance
“…Previous systematic analysis of the 50 kb of the mouse Tal1/ Pdzk1ip1 coregulatory domain ‫01מ(‬ kb to +40 kb relative to promoter 1a) has identified multiple Tal1 regulatory elements Sinclair et al 1999;Göttgens et al 2000Göttgens et al , 2002aDelabesse et al 2005). Within this well-characterized region, two novel DNaseI hypersensitive sites were identified as significantly enriched (+29 and +32) and investigated in functional assays.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous systematic analysis of the 50 kb of the mouse Tal1/ Pdzk1ip1 coregulatory domain ‫01מ(‬ kb to +40 kb relative to promoter 1a) has identified multiple Tal1 regulatory elements Sinclair et al 1999;Göttgens et al 2000Göttgens et al , 2002aDelabesse et al 2005). Within this well-characterized region, two novel DNaseI hypersensitive sites were identified as significantly enriched (+29 and +32) and investigated in functional assays.…”
Section: Resultsmentioning
confidence: 99%
“…Elements at +1 and +3, relative to the mouse exon 1a, have been shown to target the expression of Tal1 to the developing spinal cord in transgenic mice , while the +23 directs expression to specific regions within the brain (Göttgens et al 2000). The region at ‫9מ‬ functions as an enhancer in hematopoietic cell lines , and the +40 region is active in the primitive erythroid lineage (Delabesse et al 2005). The mouse +12 region is homologous to the human +14 region, which has been identified as an TAL1 transcriptional repressor (Courtes et al 2000).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies, such as those of the globin gene loci (77)(78)(79)(80)(81), the GATA1 and SCL/Tal1 gene loci (82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93), and the erythropoietin gene locus (83), characterized enhancers as distantly located, positively acting cis-regulatory elements (77,80). Recent studies have shown that enhancers have additional, complex roles in cellular gene regulation.…”
Section: Discussionmentioning
confidence: 99%
“…If the regulatory proteins of a cell as a whole are considered an input, the output is determined by the DNA sequences of the CRMs and their accessibility to transcription factor complex binding. Therefore in terms of a pression that mirrors the developmental and spatial expression patterns of the endogenous genes they regulate (Delabesse et al, 2005;Gottgens et al, 2000;Gottgens et al, 2004;Sanchez et al, 1999;Silberstein et al, 2005). Genes are equipped with multiple, disparate CRMs, each several hundred base pairs long.…”
Section: Overviewmentioning
confidence: 99%